1984
DOI: 10.1002/1097-0142(19840301)53:5<1029::aid-cncr2820530503>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response and dose-survival advantage for high versus low-dose cisplatin combined with vinblastine and bleomycin in disseminated testicular cancer a southwest oncology group study

Abstract: One‐hundred fourteen patients with advanced testicular cancer were randomized to treatment consisting of either high‐dose (120 mg/m2, monthly) or low‐dose (15 mg/m2, daily X 5 monthly) cisplatin, both combined with vinblastine and bleomycin. There were 60 (53%) complete remissions and 42 partial remissions for an overall response rate of 90%. An additional 11 patients, 4 with carcinoma and 7 with mature teratoma, following surgical cytoreduction, were rendered free of disease. There was a significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

1986
1986
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(38 citation statements)
references
References 11 publications
1
34
0
3
Order By: Relevance
“…The patient characteristics are given in Table I (Ozols et al, 1985;Levin et al, 1987;Kaye, 1992) but is controversial in other tumour types. An improvement in treatment outcome with higher than standard cisplatin doses per course was reported for non small cell lung cancer (Gralla et al, 1981;Gandara, 1989), testicular cancer (Samson et al, 1984;Ozols et al, 1988) and head and neck cancer (Forastiere et al, 1987), but randomised studies comparing standard with high cisplatin dosages (in general in day 1-5 or day 1 + 8 schedules) failed to show any benefit for the high dose arms in testicular cancer (Nichols et al, 1991), non small cell lung cancer (Einhorn et al, 1986) and malignant melanoma (Mortimer et al, 1991). Another approach to increase the platinum dose intensity is to increase the frequency of cisplatin administration, or to combine cisplatin with its analogue carboplatin.…”
Section: Resultsmentioning
confidence: 94%
“…The patient characteristics are given in Table I (Ozols et al, 1985;Levin et al, 1987;Kaye, 1992) but is controversial in other tumour types. An improvement in treatment outcome with higher than standard cisplatin doses per course was reported for non small cell lung cancer (Gralla et al, 1981;Gandara, 1989), testicular cancer (Samson et al, 1984;Ozols et al, 1988) and head and neck cancer (Forastiere et al, 1987), but randomised studies comparing standard with high cisplatin dosages (in general in day 1-5 or day 1 + 8 schedules) failed to show any benefit for the high dose arms in testicular cancer (Nichols et al, 1991), non small cell lung cancer (Einhorn et al, 1986) and malignant melanoma (Mortimer et al, 1991). Another approach to increase the platinum dose intensity is to increase the frequency of cisplatin administration, or to combine cisplatin with its analogue carboplatin.…”
Section: Resultsmentioning
confidence: 94%
“…However, in a larger study (van Eys, 1989) no difference in outcome was seen for the higher dose arm. Another study (Samson, 1984) revealed that patients with testicular cancer fared better at a higher dose level of cisplatin with an improved CR rate and survival. The dose-response effect of cisplatin in germ cell tumours has recently been confirmed by Ozols (1988), although in this study the waters were muddied by the addition of etoposide in the higher dose arm.…”
Section: Dose Escalating Studiesmentioning
confidence: 99%
“…Since the nephrotoxicity of DDP seems to be related to peak serum-free platinum levels, DDP bolus doses >100 mg m-2 would be predicted to be more toxic than smaller daily doses such as 20 mg m-2 x 5 days (Reece et al, 1987). On the other hand, reducing DDP to cumulative doses lower than 75 mg m-2 at 3 week intervals results in inferior survival in patients with metastatic germ cell cancer (Samson et al, 1984). Thus, adequate platinum dosing appears to be relevant for maintaining cure rates but may also be associated with a higher incidence of acute and late nephrotoxicity (Osanto et al, 1992).…”
Section: Discussionmentioning
confidence: 99%